114 Predicting surgical outcomes in carcinoid heart disease using transthoracic echocardiography. (17th July 2020) - Brooke, Abigail; Ahmad, Raheel; Hodosn, James; Rooney, Stephen; Oelofse, Tessa; Singh, Harjot; Shah, Tahir; Stout, Martin; Steeds, Rick
Abstract : Background: Carcinoid heart disease (CHD) develops as a complication of neuroendocrine tumours (NET). The prognosis of CHD without intervention is poor; 3 year survival is estimated at 31%. Surgical valve replacement is the only treatment for CHD, but is associated with a high 30-day mortality (10-15%) and prolonged recovery. Aim: To identify pre-operative transthoracic echocardiogram (PTTE) findings that could determine which patients have a high likelihood of post-surgical mortality at 1 year. Methods: This retrospective observational cohort study recruited 88 patients with a confirmed diagnosis of CHD between 2005-19 at University Hospital Birmingham; 49 (56%) of these were treated surgically. Indications for surgery were: stable NET, symptomatic severe valvular dysfunction, progressive RV dilatation or RV dysfunction, absence of significant comorbidities. Surgery was not offered to those patients that were unlikely to benefit, either due to frailty or short life expectancy, or if the disease severity which did not warrant surgical intervention. Patient demographics are reported in Table 1 . All patients underwent a standard PTTE. PTTE parameters assessed included: right ventricular (RV) size, RV function (qualitative), TAPSE, RV fractional area change, RV S wave velocity, left ventricular (LV) size, LV ejection fraction and valvular velocities. Surgery was performed by a single surgical team using bioprosthetic valve replacements. Across the patient population there were 48 tricuspid, 39 pulmonary, six aortic and four mitral replacements. Five patients also underwent a coronary bypass graft procedure; 12 had a patent foramen ovale closure and 23 required implantation of a permanent pacemaker. Results: Patients were followed up for a median of 15 months (IQR: 6-59) after surgery, during which time there were 33 deaths, giving a median survival time of 30 months (IQR: 7-85). Increasingly severe RV dilatation was significantly associated with shorter survival (p=0.032). The estimated survival rate at three years was 67% in those with normal RV size, compared to 24% in the severe RV group (Figure 1 ). RV basal diameter was then further assessed. ROC curve analysis for the outcome of one year survival returned an area under the curve of 0.66 (SE=0.10). Youden's index identified RV diameter >4.8cm to be the optimal cut-off for identifying high-risk patients. One year mortality rates were 26% (7/27) vs. 75% (9/12) in those with RV basal diameter of ≤4.8 vs. >4.8cm (p=0.006). Conclusion: A pre-operative right ventricular basal diameter >4.8cm is associated with a near three-fold increase in post-operative mortality at one year. These findings highlight the importance of regular imaging in order to optimise the timing of surgery in patients with CHD. Conflict of Interest: None